Qualitative exploration of the Medical Examiner role in identifying problems with the quality of patient care - O’Hara, Rachel (BMJ Open, 2021)
OBJECTIVE: A national system of Medical Examiners (MEs) implemented in England and Wales from April 2019 was intended to ensure that every death receives scrutiny from an independent, senior doctor, resulting in early detection of problems in care. The aim of this study was to increase understanding of how the ME role operates to identify problems related to quality of patient care and to explore the potential for development to maximise learning opportunities. DESIGN: A qualitative approach involved the use of semi-structured interviews. Data analysis employed a framework approach. SETTING: Study participants were recruited from 11 acute hospitals in England, known to be operating an ME service. PARTICIPANTS: A purposive sample of 20 MEs and one ME officer. RESULTS: MEs brought different perspectives to the role based on their medical background. The process for identifying and acting on quality of care concerns was broadly consistent, with a notable consensus regarding the value of speaking to bereaved relatives. Variation was identified within and between services in relation to how core components are carried out and the perceived salience of information, which appeared to reflect individual and service preferences as well as different organisational pathways. ME services required flexibility to accommodate fluctuating demand, but funding arrangements imposed restrictions. The majority of MEs highlighted limited opportunity for formal team contact and a lack of meaningful feedback as limiting scope for development. CONCLUSION: Core components of the ME role were being conducted, although individual and systemic variations in practice were identified. The discussion with bereaved relatives is a unique feature of the ME role and was considered highly valuable, both for the organisation and relatives. Further development could consider the impact of the variation identified and address mechanisms for feedback and shared learning.